FIELD THEORY IN LINGUISTICS: LEXICAL-SEMANTIC FIELDON THE EXAMPLE OF THE LEXICAL WORD “PROSPERITY” (Universal International Scientific Journal, 2026)
This article analyzes the theoretical foundations of the field theory in linguistics and its lexical-semantic field direction. The formation, basic principles, and interpretation of the lexical-semantic field theory in scientific sources are highlighted. The study demonstrates the practical application of this theory using the lexicon of “Prosperity”. The material, social, and spiritual microfields of the concept of “Prosperity” are distinguished and the semantic relationships between them are analyzed.
Keywords: field theory; lexical-semantic field; welfare lexicon